Videografi Kampanye dalam Mitos Seni Propaganda (Analisis Semiotik Terhadap Video Klip Politik Pilpres Indonesia 2014) - Vedy Santoso (Institut Seni Indonesia Yogyakarta, 2015)
Campaign Videography in Propaganda Art Myth (Semiotic Analysis towards Politics Video Clip of IndonesianPresidential Election 2014). Digital videography is one of the audio-visual work of art that developedwith the support of recording media technology. In addition to presenting the charged aesthetic value as a workof art, videography also has a function as media propaganda, as seen in the presidential election campaignvideography. In the 2014 presidential election, both candidates for president and vice president using the mediumof video as a tool to build their image in society. Effectiveness videography become the focus of the study,the extent to which the media can build a new myth in society in accordance with the imaging is presented inthe campaign video. By comparing both video campaigns of each candidate for president and vice president, wecan see how both sides provide imaging in accordance with the idealized image seoramg leader. Prabowo -Hattadescribe a leader who firmly and nationalist spirit, while Jokowi-JK portray themselves as populist leaderfigure. Then when videography charged art used for political, practical aesthetic symptoms can be translated aspropaganda art discourse by postmodern art theory. By looking at the interest of the public who enthusiasticallysupported the two presidential candidates and their representatives can be said that the image made by bothparties fairly successful. But the discourse of propaganda art is only a myth of mass culture that is momentary,because when the season finishes public campaigning has gained a new myth about the performance ofPresident. So from the phenomenon of Indonesian presidential campaign’s video in 2014 can be understoodthat the culture of democracy in Indonesia has experienced significant growth, and with the support of technologyvideography arena of ideological struggle-even extends not only affects political ideology, but also involves theideology of artists, ideology works of art, and the ideology of society into the arena.Keywords: Videography, Art Propaganda, and Myth.